2013
DOI: 10.7196/samj.7388
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of smoking and the knowledge of smoking hazards and smoking cessation strategies among HIV- positive patients in Johannesburg, South Africa

Abstract: Background While the detrimental effects of smoking among HIV positive patients have been well documented, there is a paucity of data regarding cigarette smoking prevalence among these patients in South Africa. Objectives To establish the frequency, demographics, and knowledge of harmful effects and of smoking cessation strategies among HIV-positive patients in Johannesburg, South Africa. Methods A prospective cross-sectional survey, using a structured questionnaire interview, of HIV-positive patients atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
3
28
0
2
Order By: Relevance
“…5 The prevalence found in this study was slightly lower than the reported national prevalence for tobacco use: 18.1%, 16.9% and 17.6% in 2010, 2011 and 2012, respectively. 16,21,22 However, our result was similar to a report by Waweru et al, 28 which found a smoking prevalence of 15% among adults in Johannesburg, South Africa. In South Africa, the prevalence of smoking was reported to have modestly reduced between 2004 and 2014, from 24% to 20%; however, there was no reduction in the number of smokers, due to population growth.…”
Section: Discussionsupporting
confidence: 91%
“…5 The prevalence found in this study was slightly lower than the reported national prevalence for tobacco use: 18.1%, 16.9% and 17.6% in 2010, 2011 and 2012, respectively. 16,21,22 However, our result was similar to a report by Waweru et al, 28 which found a smoking prevalence of 15% among adults in Johannesburg, South Africa. In South Africa, the prevalence of smoking was reported to have modestly reduced between 2004 and 2014, from 24% to 20%; however, there was no reduction in the number of smokers, due to population growth.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, in Sub-Saharan Africa, the prevalence of cigarette smoking appears to be much lower among MLHIV and especially among WLHIV. A smoking prevalence study out of South African suggests 23.2% of MLHIV in the region and 7.4% of WLHIV in the region report active cigarette smoking (89). Among PLHIV, smoking is known to enhance systemic immune activation(83) and augment the risk of select CVD and NADC(90) .…”
Section: Heightened Systemic Immune Activation/inflammation Among Wlhivmentioning
confidence: 99%
“…However, it was lower in this study which is 0.7%. The prevalence of current smoker is 1.2% which is not significant compared to similar studies done in South Africa (15%), in Vietnam (36.1%), in Birmingham University (39%), Uruguay (42.4%) and China (62%) [18,[22][23][24]. Thus the prevalence of current smoking among HIV infected person is considerably higher worldwide due to urbanization, civilization and higher educational level.…”
Section: Discussionmentioning
confidence: 58%